Students’ Perception on the Use of Google Translate for English Learning - Sofia Nur Agustin; Siswana Siswana (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
The popularity of Google Translate as a media in translating languages is growing fast on the internet. Through Google Translate, it has become an alternative way for students to translate or understand learning English. This study aims to describe students’ perception of the use of Google Translate in English Learning in SMKN 62 Jakarta. This study was conducted a qualitative analysis using a questionnaire and interview which participate of 5 Senior High School students who had the experience in using Google Translate in English Learning. In collecting the data, this study used a 4-point Scale Likert questionnaire to find out the response of students’ perceptions about the use of Google Translate for learning English. The collected data was done through a semi-structured interview to examine how students perceive the use of Google Translate in their learning. Interviews are going to gain more details of respondents' thoughts. The result of this study showed that students’ perception of the use of Google Translate in English class is positive. Google Translate helps them to translate and gives them more understanding of English. It is indicated that Google Translate generously helps a lot. Students can translate quicker and complete their task. Even though there is still weakness in translation using Google Translate, Google Translate saves time on translating English. Keywords: Perception, Google Translate, English Translate